Financial Literacy And Inclusion Of Farmers And Fishermen: A Case Study In Tawiri Village And Dusun Seri Ambon City Island, Maluku Indonesia - Patricya F. V. Pattipeilohy; S. F. W. Thenu; I. T. Matitaputty; Wardis Girsang (Eduvest - Journal of Universal Studies, 2024)
Financial literacy and financial inclusion are needed to improve people's lives through Financial Services Institutions. The 2016 and 2019 National Surveys on Financial Literacy and Inclusion show that the financial literacy index of farmers and fishermen is the lowest compared to other types of work. Indonesia has considerable potential for agricultural land and marine fisheries, especially in Ambon City. This study aims to determine the effect of financial literacy on financial inclusion for farmers and fishermen. The research method is a survey of 65 households of farmers and fishermen—data analysis using SMART PLS4.0 software. The results showed that knowledge or literacy and attitudes affect skills, while skills affect access. Furthermore, access and trust affect inclusion. The implication is that improving skills and attitudes will improve access; access affects trust, which determines financial inclusion.